Comparing Oral and Written Cooking Recipes Using Systemic Functional Grammar - Esti Sugiharti (Jurusan Bahasa Inggris - Politeknik Negeri Bandung, 2021)
This article compares oral and written cooking recipes of the same food created by the same person, by using systemic functional grammar. The aim of the article is to find out the similarities and differences of the language used in both recipes. The data are obtained from Jamie Oliver’s cooking show aired in a YouTube channel on how to make scones and the written recipe of the same food published in his website. The focus of the analysis is on the lexico-grammar of the clauses used in the texts. The result shows that there are more differences than similarities between the two texts. There are more clauses in the spoken text than those in the written text in terms of quantity and variety. In the ideational function, both texts have a similar variety of processes with the majority of material process showing imperatives of procedural texts and additional information using mental, existential, and relational processes, but in the written text there are two clauses using verbal process that are not found in the spoken text. In the interpersonal function, the two texts show demands of good and services and the use of modalities in expressing the expected results of the cooking process. In the spoken text, the relation between the cook and the audience is friendlier and closer than that in the written text. It is demonstrated in the use of vocatives and interrogatives that are not used in the written text. The textual functions show similar results in the use of conjunctions but the spoken text displays closer interpersonal textual functions found in the use of vocatives. The analyses of the three metafunctions of the two recipes may contribute to the study of food texts in linguistics that are relatively low compared to those in other disciplines.